Effects of implant thread design on primary stability-a comparison between single- and double-threaded implants in an artificial bone model - Yoko Yamaguchi; Makoto Shiota; Masaki Fujii; Masahiro Shimogishi; Motohiro Munakata (SpringerOpen, 2020)
Abstract Background Primary implant stability is essential for osseointegration. To increase stability without changing the implant size, the thread length must be extended by reducing pitch, using a double-threaded implant, or reducing pitch/lead and lead angle to half that of a single-threaded implant. Materials and methods We tested the stabilities of these configurations using artificial bone. A 1.2-mm pitch, single-threaded implant (12S) was the control. We tested a 0.6-mm pitch/1.2-mm-lead double-threaded implant (06D) and a 0.6-mm pitch/lead single-threaded implant (06S). We compared stabilities by measuring insertion torque, removal torque, and the implant stability quotient (ISQ). Damage to bone tissue caused by the implants was evaluated using microscopy and morphometric analysis. Results We show that 06D and 06S significantly improved stability compared with the 12S reference. The stability of 06S was significantly greater compared with that of 06D, except for ISQ. The three implants were associated with bone tissue damage characterized by debris and voids surrounding the implant/bone interface. The 06D caused the most tissue damage, followed by 06S and then 12S. Conclusion These findings indicate that primary stability was significantly improved by changing the implant size, extending the thread length with reduced pitch/lead, and reducing the lead angle to half that of a single-threaded implant compared with a double-threaded implant.